Infrared Spectroscopic Evidence Supporting Heterogeneous Site Binding Models for Humic Substances - Lumsdon, David G; Fraser, Anthony R (Environmental science & technology, 2005)
Infrared spectroscopy was used to corroborate predictions made by newly developed heterogeneous site binding models for humic substances. Experimental conditions to acquire the spectra of soil humic substances (humic and fulvic acid and a polysaccharide fraction) in an aqueous state using horizontal attenuated total reflectance Fourier transform infrared spectroscopy (HATR−FTIR) were established. Elimination of the water spectrum from that of the sample was achieved by spectral subtraction of the water peak at 2020 cm-1. A KSCN internal standard with an absorption band at 2067 cm-1 was used to verify the efficacy of the subtraction procedure. Spectral artifacts produced by the water spectrum subtraction and from contaminants within the humic materials have been identified. Three fulvic and one humic acid solution were examined in solutions of varying pH. Results show that the observed proportion of ionized carboxylate in relation to pH is consistent with models that assume electrostatic effects and a continuous distribution of proton association constants (log K H). The spectroscopic data were in accordance with calculations made using the generic humic and fulvic acid NICA−Donnan model parameters.